Pengaruh Marketing Mix Terhadap Loyalitas Pelanggan di Q-Mart 1 Super Store Kota Gorontalo - Adelia Amrin; Sudirman (Jurnal Pendidikan Ekonomi dan Bisnis, 2025)
The objective of this study was to determine the effect of marketing mix on customer loyalty at Q-Mart 1 Super Store, Gorontalo City. The research employed a quantitative approach with a survey resereach method. Additionally, the data used were primary data obtained from distributing questionaires to customers at-Qmart 1 Super Store, Gorontalo City, with a total sample of 30 respondents. The data analysis technique was done through simple linear regression. The findings denoted that marketing mix affected customer loyalty at Q-Mart 1 Super Store, Gorontalo City. The effect of the marketing mix on costumer loyalty was 28.7%, while the remaining 78,3 was affected by other variables that were not examined in this research.